2021
DOI: 10.1007/978-3-030-86797-3_33
|View full text |Cite
|
Sign up to set email alerts
|

Crowd Analysts vs. Institutional Analysts – A Comparative Study on Content and Opinion

Abstract: The ongoing digital transformation shapes the world of information discovery and dissemination for investment decisions. Social investment platforms offer the possibility for non-professionals to publish financial analyst reports on company development and earnings forecast and give investment recommendations similar to those provided by traditional sell-side analysts. This phenomenon of "crowd analyst reports" has been found to provide an adequate alternative for non-professional investors. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Most academic literature has found that soft dollar arrangements result in agency conflicts (Bender et al, 2021). Empirical evidence shows that misaligned incentives have been reduced through MiFID II (Lourie et al, 2020), also indicated by the increase in quality in sell-side research (Bankamp et al, 2021;Fang et al, 2020;Guo and Mota, 2021;Lang et al, 2019;Pope et al, 2019)-albeit tipping still remains (Ludolph, 2021) and banks might instead steer their recommendations to private investors more opportunistically (Fecht et al, 2021). Still, as there is less trade-generating research and more high-quality research, funds are hypothesized to spend less on execution that is detrimental for fund performance.…”
Section: Insert Table 1 About Herementioning
confidence: 99%
See 1 more Smart Citation
“…Most academic literature has found that soft dollar arrangements result in agency conflicts (Bender et al, 2021). Empirical evidence shows that misaligned incentives have been reduced through MiFID II (Lourie et al, 2020), also indicated by the increase in quality in sell-side research (Bankamp et al, 2021;Fang et al, 2020;Guo and Mota, 2021;Lang et al, 2019;Pope et al, 2019)-albeit tipping still remains (Ludolph, 2021) and banks might instead steer their recommendations to private investors more opportunistically (Fecht et al, 2021). Still, as there is less trade-generating research and more high-quality research, funds are hypothesized to spend less on execution that is detrimental for fund performance.…”
Section: Insert Table 1 About Herementioning
confidence: 99%
“…First, to the best of our knowledge, there is no empirical evidence on the impact of separating research from execution costs on fund investors, even though MiFID II prominently discusses and targets corresponding conflicts of interest between asset managers and their clients (Guo and Mota, 2021). The related literature has so far focused exclusively on the consequences for sell-side research providers (Anselmi and Petrella, 2021;Bankamp et al, 2021;Fang et al, 2020;Fecht et al, 2021;Fu et al, 2021;Guo and Mota, 2021;Kim et al, 2021;Lang et al, 2019;Liu and Yezegel, 2020;Lourie et al, 2020;Pope et al, 2019). Given the original motivation for the regulation, studying the impact on fund investors, however, seems particularly relevant for ongoing debates among academics, policy-makers and practitioners about the costs and benefits to unbundle payments (Di Maggio et al, 2022).…”
Section: Introductionmentioning
confidence: 99%